Biological anthropology - Park, Michael Alan (McGraw Hill, 2008)
This concise introduction to biological anthropology discusses the core areas of the discipline within a unique framework modeled on the scientific method. The text emphasizes themes and theories: facts are presented as supportive evidence rather than dissociated pieces of information. Each chapter poses questions that get at the heart of the field, answers them, and then reexamines them in the same way that scientists generate and test hypotheses. Unlike all other brief biological anthropology texts, this is not an abridged version of a longer text. Its presentation is fluid, well integrated, and covers all the standard topics in a carefully managed level of detail. Well-paced explanations, an inviting tone, and examples of the everyday uses of biological anthropology make the text a pleasure to read.